2019
DOI: 10.46657/ajresd.2019.1.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of Solar Radiation using an Empirical Model

Abstract: Global demand for energy is increasing rapidly and natural energy resources such as oil, gas and uranium are declining due to the widespread diffusion and development of the industry in recent years. To cover energy needs, research is being conducted on renewable energy. One of the renewable energies that can meet the world's demand so far is solar energy, which is free and inexhaustible in most parts of the world, and it has become an economic source. In this article we will make a forecast of the empirical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In theory, the performance of solar collector depends on climatic conditions and several operating condition such as collector orientation and slope, thickness of cover materials, wind speed, collector length, collector depth, and the material of absorber [5,6]. The objective of the present study was to investigate the effect of the double-glazing on the performance of an air solar collector in the climatic conditions of Adrar region [7].…”
Section: Introductionmentioning
confidence: 98%
“…In theory, the performance of solar collector depends on climatic conditions and several operating condition such as collector orientation and slope, thickness of cover materials, wind speed, collector length, collector depth, and the material of absorber [5,6]. The objective of the present study was to investigate the effect of the double-glazing on the performance of an air solar collector in the climatic conditions of Adrar region [7].…”
Section: Introductionmentioning
confidence: 98%
“…Although it is a permanent source, it may be absent in some cases, but we need all the day to solve this problem, it is recommended to think of finding a way to store the energy released by the sun. [5] Fillali Mustafa et al [6], present a simulation by using the Atlas-Silvaco to show the role of doping the lower window layer on the performances of tandem CS in InGaP / GaAs with a tunnel heterojunction. The results show that the conversion efficiency obtained for the tandem slar sell without the window layer of the lower cell is around 22.1823%.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, differences in supply and demand in electricity grids have already had to be matched. To store the excess capacity at night and ensure availability during high consumption hours, energy has been stored in the gravitational potential using hydropower plants for many decades [5]. Previous studies in this field confirmed that electrochemical storage will be a very important part of energy systemsfuture.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic information systems bring together different computer methods and techniques, making it possible to model, enter in digital form, store, manage, consult, analyze, represent objects or collections of geographic objects, with the essential particularity of taking take into account the spatial characteristics of these objects in the same way as the descriptive attributes attached to them. In fact, the name "GIS" covers a wide variety of software implementations built according to different technical choices, with very diverse functionalities and performances [4][5][6].…”
Section: Introductionmentioning
confidence: 99%